ANALISIS PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN DAN DAMPAKNYA PADA LOYALITAS KONSUMEN DALAM MENGGUNAKAN JASA TRANSPORTASI KERETA API : STUDI KASUS STASIUN INDIHIANG - Risdianto; Herman (Melati Institute, 2023)
Improving the quality of service is very important in the sustainability of a company, especially nowadays the changing paradigm of global scale competition has begun to demand a basic shift in the business world, the basic mission of a business is no longer in the form of profit but to provide added value to consumers with the aim of creating satisfied and loyal customers. Therefore, to win the competition by improving the quality of services that have been implemented so far is very important. Departing from the above, this study aims to determine the effect of service quality on consumer satisfaction and its impact on consumer loyalty in using rail transportation services. The research results state that Service quality has a significant effect on consumer satisfaction. Service quality has a significant effect on consumer loyalty. Service quality has a significant effect on consumer loyalty through consumer satisfaction.